DELTA FM JOGJA'S MARKETING COMMUNICATION STRATEGY IN MAINTAINING ITS EXISTENCE IN THE SPECIAL REGION OF YOGYAKARTA - Evanny Yuwike Permata; Panji Dwi Ashrianto (The Indonesian Journal of Communication Studies, 2021)
The intence radio competition in Yogyakarta requires radios to have a strategy in maintaining their existence in this digitalized era. A good marketing communication strategy is needed to attract the attention of both listeners and advertisers. Delta FM radio as a network radio certainly has challenges in competing with other competitor radios in Yogyakarta. To maintain its existence, Delta FM radio requires the right marketing communication strategy. This study aims to determine the marketing communication strategy of Delta FM Yogyakarta in maintaining its existence in D.I.Yogyakarta. This study uses Planning theory by Berger, Marketing Communication Mix, and analysis of Segmenting, Targeting, and Positioning (S-T-P). The research method used is descriptive qualitative. The results showed that in determining the marketing communication strategy, Delta FM Yogyakarta carried out 3 stages, namely the planning stage, the implementation stage, and the evaluation stage. In its implementation, Delta FM uses 5 stages of marketing communication mix, such as Advertising, Sales Promotion, Public Relations, Personal Selling and Direct Selling.